Annual variations in earthworm surface-casting activity and soil transport by water runoff under a temperate maize agroecosytem - Le Bayon, Renée-Claire; Corrie Moreau; Chantal Gascuel-odoux; Binet, Françoise (Elsevier, 2002)
Investigations were conducted on both the annual patterns of earthworm casting activity and the annual variations in soil and phosphorus (P) transfers by water runoff, under a temperate maize crop, to determine whether there is any time synchronism over the year between these processes that could increase risk of soil erosion. Cast dynamics were measured at 15-day intervals for 1 year. Phosphorus forms were determined in runoff waters and the sediments collected were analyzed for nitrogen (N), carbon (C) and P contents. As long as there was no crust at the soil surface, no runoff was observed. Once the sealing crust formed, the soil erosion began. After the rainstorm events in August, soil erosion already reached 70% of the total soil loss that occurred over the crop year. A total of 140 g m−2 year−1 of sediment was lost by the end of the year. A time synchronization was observed between tillage practices and highest cast productions over the year, which were then interrupted for up to 5 weeks after both ploughing and crop harvest. In particular, the absence of anecic casts onto the soil till September underline that Lumbricus terrestris was most affected by ploughing. The likelihood that earthworm casts contributed to soil erosion was enforced by the correlation between the timing of cast disappearance and the increase in sediment transfers for rainstorm events observed in summer, as well as for long rainy period in fall/winter. However, we could not outline a systematic correlation over the year but just for defined periods. Particulate soil erosion and P amounts in runoff waters decreased (55–2 g m−2, and 19–5 mg of P losses m−2, respectively) through the crop year. However, the content of organic matter in sediment increased (2.54–5.16%) compared to the initial soil (1.8%), as well as the P concentration (1.1–1.6 mg g−1).
Keywords: Soil erosion; Water runoff; Earthworms; Surface-casts; P; Maize crop